Patched regulates lipid homeostasis by controlling cellular cholesterol levels - Carla E. Cadena del Castillo; J. Thomas Hannich; Andres Kaech; Hirohisa Chiyoda; Jonathan Brewer; Masamitsu Fukuyama; Nils J. Færgeman; Howard Riezman; Anne Spang (Nature Communications, 2021)
Cellular cholesterol levels are tightly regulated. Here, the authors show that the hedgehog signalling receptor PTCH is a cholesterol transporter. Reduction in PTCH activity leads to cellular cholesterol accumulation, changes in nuclear hormone receptor activity and fatty acid metabolism.